PERLINDUNGAN TERHADAP KREDITUR PEMEGANG JAMINAN FIDUSIA ATAS HAK CIPTA KONTEN YOUTUBE - Mayshinta, Aura; Ahmad, Muh. Jufri (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Youtube content copyrights are intangible movable assets, which can be used as the objects for fiduciary guarantees in financial institutions when it meets the requirements set out in Article 10 of The Government Regulations Number 24 Year 2022 regarding Implementation of Law Number 24 Year 2019 concerning Creative Economy. However, the provisions in this article give rise to many speculations as criteria regarding youtube content copyrights which are going to be made as objects for fiduciary guarantees are not specifically regulated. Hence, the researcher wanted to examine how is the protection of creditors who hold fiduciary guarantees with their youtube content copyrights?. This article is normative research with statutes approach and conceptual approach, which is carried out by analyzing primary legal materials and secondary legal materials that have something to do with the problem under study. The results of the research proposed that Law Number 10 Year 1998 which is the amendment for Law Number 7 Year 1992 concerning Banking, instructs banks when extending credit to apply the precautionary principle in assessing personal customers, customer businesses and rights copyright youtube content as collateral object. When evaluating the collateral object, protection will be found for copyright holders of youtube content through the tools provided by youtube, namely the content verification programs, copyright match tool (CMT), and content id. If there has been a default in the credit agreement, then based on Law Number 42 Year 1999 concerning Fiduciary Guarantees regulate, the creditor can execute the copyright of youtube content which is the object of collateral